2022
DOI: 10.12968/jowc.2022.31.9.792
|View full text |Cite
|
Sign up to set email alerts
|

Complex decongestive therapy in a patient with poliomyelitis, bilateral lymphoedema and a deep wound: a case study

Abstract: Objective: The aim of this case report is to describe the results of complex decongestive therapy (CDT) in a patient with poliomyelitis and bilateral lymphoedema, and to emphasise the effect of CDT on wound healing. Method: A 48-year-old female patient was given CDT for bilateral grade 3 lymphoedema in the lower extremities and a deep wound on the right foot. She had been diagnosed with poliomyelitis sequela and mobilised with a wheelchair for 26 years. The lymphoedema on both legs and the wound on the right f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Our total treatment duration was 3 weeks, which is consistent with the treatment duration emphasized in the study by Qiao et al [39]. In a case report published by Borman et al [40], a 48year-old woman with polio sequelae who was mobilized with a wheelchair and had lymphedema and infected wounds in both lower extremities was mentioned. It was reported that significant improvements in extremity volumes and wound healing were achieved by applying a 4-week course of 20 sessions of skincare education, MLD, exercise, and bandaging treatment [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our total treatment duration was 3 weeks, which is consistent with the treatment duration emphasized in the study by Qiao et al [39]. In a case report published by Borman et al [40], a 48year-old woman with polio sequelae who was mobilized with a wheelchair and had lymphedema and infected wounds in both lower extremities was mentioned. It was reported that significant improvements in extremity volumes and wound healing were achieved by applying a 4-week course of 20 sessions of skincare education, MLD, exercise, and bandaging treatment [40].…”
Section: Discussionsupporting
confidence: 87%
“…In a case report published by Borman et al [40], a 48year-old woman with polio sequelae who was mobilized with a wheelchair and had lymphedema and infected wounds in both lower extremities was mentioned. It was reported that significant improvements in extremity volumes and wound healing were achieved by applying a 4-week course of 20 sessions of skincare education, MLD, exercise, and bandaging treatment [40]. In another study, it was observed that a 20-session complex decongestive therapy was beneficial in reducing extremity volume and alleviating symptoms of depression and anxiety in 27 patients with unilateral lower extremity lymphedema [41].…”
Section: Discussionmentioning
confidence: 99%